Germline large genomic alterations on 7q in patients with multiple primary cancers - Villacis, R. A.R.; Basso, T. R.; Canto, L. M.; Nóbrega, A. F.; Achatz, M. I.; Rogatto, S. R. [UNESP] (Springer Nature, 2017)
Patients with multiple primary cancers (MPCs) are suspected to have a hereditary cancer syndrome. However, only a small proportion may be explained by mutations in high-penetrance genes. We investigate two unrelated MPC patients that met Hereditary Breast and Ovaria Cancer criteria, both presenting triple negative breast tumors and no mutations in BRCA1, BRCA2 and TP53 genes. Germline rearrangements on chromosome 7q, involving over 40 Mb of the same region, were found in both patients: one with mosaic loss (80% of cells) and the other with cnLOH (copy-neutral loss of heterozygosity) secondary to maternal allele duplication. Five children tested had no alterations on 7q. The patients shared 330 genes in common on 7q22.1-q34, including several tumor suppressor genes (TSGs) previously related to breast cancer risk and imprinted genes. The analysis of the triple negative BC from one patient revealed a mosaic gain of 7q translated for over-expressed cancer-related genes. The involvement of TSGs and imprinted genes, mapped on 7q, has the potential of being associated to MPC risk, as well as cancer progression. To our knowledge, this is the first description of patients with MPCs that harbor constitutive large alterations on 7q.